Aplikasi Web Sistem Irigasi dan Monitoring Lahan Reklamasi Bekas Tambang Batubara - Fattah, Nazar Abdul; Sari , Wahyuni Eka; Irwansyah, Irwansyah (Jurnal Ilmu Siber dan Teknologi Digital, 2025)
Purpose: This study develops a web application for PT Insani Baraperkasa to streamline vegetation management on post-reclamation mining land. The system enhances efficiency via real-time monitoring, automated scheduling for irrigation and fertilization, and integrated Internet of Things (IoT) device control. Methodology/approach: Built on the Waterfall model, the system uses a Laravel backend, Vue.js frontend, and MySQL with MQTT for IoT communication. As a foundational study, validation focused on core functionality using white-box (PHPUnit) and black-box (Postman) testing to verify logic and API integrity. This approach covered all 25 application endpoints, ensuring comprehensive functional for the initial development phase. Results/findings: Backend stability was validated by 25 successful endpoint tests, executing in 2.61s (PHPUnit) and 4.242s (Postman). Real-time IoT communication via MQTT proved highly responsive with low average latencies (7ms native; 89ms WebSocket), ensuring effective remote monitoring and control. Conlusion: The research has successfully developed a centralized digital tool that optimizes vegetation maintenance. The application enhances operational efficiency for PT Insani Baraperkasa and improving the consistency of environmental management. Limitations: The scope was confined to the development of a bespoke web application, not commercialization. Consequently, it lacks a multi-tenant architecture and a native mobile app. Further evaluations, such as load and usability testing, were considered beyond the scope of this initial development phase. Contribution: This study contributes a functional and reliable IoT-based application for enhancing vegetation maintenance at PT Insani Baraperkasa. The successful deployment serves as a practical, scalable proof-of-concept, demonstrating the effectiveness of digital tools in managing post-reclamation land.